Direct-Acting Antivirals in Hepatitis C Treatment for Renal Impairment: Liver Safety Concerns and Effectiveness in Peritoneal Dialysis - Hsuan-Yu Hung; Wei-Liang Hung; Ye Gu; Chung-Yu Chen (Biomedicines)
Background/Objectives: Glecaprevir/pibrentasvir (G/P) and elbasvir/grazoprevir (EBR/GZR) are effective treatments for chronic hepatitis C (CHC), especially in patients with chronic kidney disease (CKD). However, both regimens carry a risk of drug-induced liver injury (DILI). This study investigates the association between renal failure and DILI, using real-world data, and assesses the effectiveness of these treatments in peritoneal dialysis patients. Methods: A retrospective cohort study was conducted using data from the Ditmanson Research Database, including patients with CHC treated with G/P or EBR/GZR from 1 August 2017 to 31 December 2020. Patients were categorized into CKD and normal kidney function (NKF) groups. Two sensitivity analyses were performed to assess DILI risk. The study was approved by the DMF-CYCH Institutional Review Board (CYCH IRB No.: 2021010). Results: In 837 patients, DILI risk, expressed as incidence rate ratios (IRR), was 0.64 (95% CI 0.25–1.63) in the NKF group and 1.29 (95% CI 0.12–14.23) in the CKD group. Sensitivity analyses showed consistent results. A case–time–control analysis suggested liver instability despite treatment, with comorbid liver tumors (aOR 18.89; 95% CI 5.4–66.12) and hypertension (aOR 4.25; 95% CI 1.49–12.15) linked to higher DILI risk. All peritoneal dialysis patients (n = 10) achieved a 100% SVR12 rate. Conclusions: This real-world study supports the effectiveness of G/P and EBR/GZR in peritoneal dialysis patients. Comorbidities that impair liver function are key predictors of abnormal liver parameters, highlighting the need for careful monitoring during CHC treatment.